10 minutes 38 second in this strange world - "Shafak, Elif" (Viking Books London, 2003)
'In the first minute following her death, Tequila Leila's consciousness began to ebb, slowly and steadily, like a tide receding from the shore. Her brain cells, having run out of blood, were now completely deprived of oxygen. But they did not shut down. Not right away ... ' Our brains stay active for ten minutes after our heart stops beating. For Tequila Leila, each minute brings with it a new memory - growing up with her father and his two wives in a grand old house in a quiet Turkish town; watching the women gossip and wax their legs while the men went to mosque; sneaking cigarettes and Western magazines on her way home from school; running away to Istanbul to escape an unwelcome marriage; falling in love with a student who seeks shelter from a riot in the brothel where she works. Most importantly, each memory reminds Leila of the five friends she met along the way - the friends who are now desperately trying to find her."--Publisher description